Analysis of disproportionation process of trifluoroethylene using high power spark ignitions over 5 J. (January 2018) - Otsuka, Tetsuo; Ueno, Katsuya; Okamoto, Hidekazu; Ippommatsu, Masamichi; Dobashi, Ritsu
Abstract: Trifluoroethylene and its mixtures are useful as next generation refrigerants because of their lower global warming potential (GWP) than that of those ordinarily used. Trifluoroethylene, however, has the potential to disproportionate explosively, as does tetrafluoroethylene. In the present research, we quantitatively searched for conditions in which trifluoroethylene undergoes disproportionation. We modified the ignition apparatus as so it could be performed using electromagnetic force, we simulated spark phenomena in air conditioners and analyzed the disproportionation process of trifluoroethylene using that equipment. The spark energy yielding 1% probability of disproportionation was found to be 6.33 J, at which pressure was 1 MPa and temperature was 373 K. It was revealed that trifluoroethylene had much higher minimum ignition energy than that of ordinary combustible materials such as methane and hydrogen. The reason for the high ignition energy needed to initiate disproportionation of trifluoroethylene was considered to be that the flame kernel needed to have a large size and a long lifetime to propagate the disproportionation reaction because of its lower frequency factor of producing solid graphite. The fact that the delay time of trifluoroethylene disproportionation was 0.1 s also explained the lower frequency factor of producing solid graphite. Highlights: The disproportionation probability of trifluoroethylene (HFO-1123) was related to ignition energy. The energy at 1% disproportionation probability of HFO-1123 was 6.33J and was much larger than those of hydrocarbons' combustion. It was presumed Carbon precipitation through disproportionation of HFO-1123 was the cause of larger minimum ignition energy. We modified the ignition apparatus as so it could be performed using electromagnetic force under high pressure conditions.